Deteksi Dini Tanaman yang Mengalami Kekurangan Air untuk Menentukan Waktu Pengairan - Andi Bahrun (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
Detection of water stress in olants may help to schedule irrigation and improve water use efficiency. The objective of this study was to determine the reflectance vegetation index (RVI) obtained from remote sensing of the crops duringg soil drying and fully watered plots as a tool for detection of water stress. RVI was calculated from incoming (PARi) and reflected (PARc) photosynthetically active radiation and from incoming (NIi) and reflected (NIc) near infrared radiation using the equation RVI = (NIc / NIi) / PARc / PARi). the effect of soil drying on leaf expansion, biomass accumulution, abscisic acid (ABA) in xylem sap and leaf water potential were used as drought indicators in maize grown in lysimeter in the field. Leaf area expansion and biomass acimulation were decreased by drought. The reflectance vegetation index was measured when green crop area index increased during the vegetation stage of growth. Xylem (ABA) increment coincided with decrease in RVI of drought plants. Changes in RVI of drought plants which were compared to RVI of fully irrigated reference plants occurred at early stage of drought stress when relative available soil water content was 60%. RVI was higly correlated with green crop area index (R2 = 0.84) and biomass accumulation (R2 = 0.88). We suggest that measurements of RVI in drought field plants compared to RVI measurements of fully irrigated reference plants within the same field can be used as an early warning system of irrigation.Keyword : Abscisic acid, Drought Reflectance, Water